2022
DOI: 10.3329/jrpmc.v7i2.62638
|View full text |Cite
|
Sign up to set email alerts
|

Ramadan Risk Stratification by International Diabetes Federation and Diabetes & Ramadan International Alliance (IDF-DAR) Risk Calculator in Bangladeshi People with Diabetes Mellitus who wished to Fast in 2022

Abstract: Background: Risk stratification is an essential and first component of the pre-Ramadan assessment of patients with diabetes mellitus (DM) who wish to fast. Limited data are reported from Bangladesh regarding risk stratification of people with DM who wish to fast. Objective: To determine the risk status of people with DM who wish to fast during Ramadan. Methods: This cross-sectional observational study was done among Muslim people of DM with at least one year of experience of Ramadan in previous yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Regular blood glucose monitoring: Patients need to be encouraged to self-monitor glucose up to two times a day if at moderate risk of hypoglycemic episodes. However, if elevated risk is observed, a 7-point time scale monitoring method is recommended daily[ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regular blood glucose monitoring: Patients need to be encouraged to self-monitor glucose up to two times a day if at moderate risk of hypoglycemic episodes. However, if elevated risk is observed, a 7-point time scale monitoring method is recommended daily[ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…The reliability of this new scoring system has been assessed in a few studies. 4 , 5 , 7 - 9 A recent study by Mohammed et al, 4 from the United Arab of Emirates, assessed this score ability to predict the likelihood of patients with diabetes fasting and the risks from fasting, mostly type 2 diabetes mellitus (T2DM) patients (91.5%), and discovered that this tool correctly predicted both one’s capacity to observe fasting during Ramadan and the tendency to develop hypo- or hyperglycemia. On the other hand, another study carried out at several diabetes clinics in Bangladesh with 1328 T2DM participants (the DAR-BAN study), concluded that this scoring system is more careful in how it categorizes T2DM patients’ risks from fasting.…”
mentioning
confidence: 99%